C-terminal peptide identification by fast atom bombardment mass spectrometry. - Rose, K (1988)
A previously described technique [Rose, Simona, Offord, Prior, Otto & Thatcher (1983) Biochem. J. 215, 273-277] permits the identification of the C-terminal peptide of a protein as the only peptide that does not incorporate any 18O upon partial enzymic hydrolysis in 18O-labelled water. Formation of chemical derivatives followed by combined g.l.c.-m.s. was used in this earlier work. We now describe the isolation from protein digests, by reversed-phase h.p.l.c., of labelled and unlabelled polypeptides and their direct analysis by fast atom bombardment mass spectrometry. Under the conditions used, the 18O label is retained throughout the separation and analysis, thus permitting assignments of C-terminal peptides to be made. Enzyme-catalysed exchange of label into the terminal carboxy group was found to occur in some cases without hydrolysis of a peptide bond. This effect, which may be exploited to prepare labelled peptides, does not prevent application of the method (two separate digests must then be used). We have applied our method to the analysis of enzymic partial hydrolysates of glucagon, insulin and of several proteins produced by expression of recombinant DNA.